P60 Outcomes of pregnancy in women with bronchiectasis. (15th November 2017) - Taylor, SEG; Flight, WG
Abstract : Introduction: The impact and outcomes of pregnancy in women with non-cystic fibrosis bronchiectasis are largely unknown. Methods: We performed a retrospective cohort study of pregnancy in women with bronchiectasis attending our centre between 2007–2017. In all cases the mother had been diagnosed with bronchiectasis prior to conception and was under close monitoring throughout the pregnancy. Baseline descriptive statistics recorded included: maternal age at delivery, body mass index (BMI), disease aetiology, previous pregnancy, and baseline percentage predictive values for respiratory function 6 months prior to conception assessed using forced expiratory volume in 1 s (FEV1 ) and forced vital capacity (FVC). Longitudinal statistics were recorded for outcome of pregnancy, mode of delivery, infection status, obstetric cholestasis and haemoptysis during pregnancy, and respiratory function at baseline (6 months prior to gestation), conception, delivery and 6 months postpartum. Statistical analysis was made using the Pearson's two-tailed correlations, with p-values of <0.05 considered as statistically significant. Results: There were 11 successful pregnancies in 10 women with bronchiectasis during the study period. In all cases pregnancy was well tolerated with no significant adverse events. Mean age was 33.9 (range 23.9–43.5). Evidence of negative investigations for cystic fibrosis was found in 9/10 patients. Mean baseline FEV1 prior to pregnancy was 70.2%-predicted (SD 19.6) compared with 66.5% (SD 20) at delivery (p≥0.05) and 66.2% (SD 20.7) at 6 months after delivery (p≥0.05). FEV1 /FVC ratio at conception, delivery and at 6 months after delivery was 0.77 (SD 0.1), 0.75 (SD 0.1) and 0.73 (SD 0.1) respectively (p≥0.05). 60% of women had positive sputum cultures during pregnancy: Pseudomonas aeruginosa in 27.3%, Haemophilus influenzae 45.5%, Staphylococcus aureus 18.2%, Streptococcus pneumoniae 9.09% and coliforms 9.09%. Positive sputum microbiology was not correlated with any change in respiratory function or pregnancy outcomes. Conclusion: Pregnancy in women with non-CF bronchiectasis was largely well tolerated in our cohort. Larger studies are needed to determine the true impact of pregnancy on lung function in this population.